2001
DOI: 10.1109/55.919227
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the InGaAs hole impact ionization coefficient in InAlAs/InGaAs pnp HBTs

Abstract: The hole multiplication factor in pnp InAlAs/InGaAs single heterojunction bipolar transistors (HBTs) has been measured as a function of the base-collector bias. The hole impact ionization coefficient beta (p) has been estimated taking into account the Early effect, I-CBO, and thermal effects. Numerical corrections for dead space were made. The importance of considering second order effects is highlighted, showing that rough approximations can lead to an overestimation of the coefficient beta (p). At low electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
2
8
2
Order By: Relevance
“…Although the results in [1] and [2] agree at higher fields, the values of are in disagreement with those in [5] and [6] for fields below 200 kVcm . By contrast, the recent HBT measurements of [7], [8], which agree qualitatively with those reported in [5], [6] did not show this low field impact ionization.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…Although the results in [1] and [2] agree at higher fields, the values of are in disagreement with those in [5] and [6] for fields below 200 kVcm . By contrast, the recent HBT measurements of [7], [8], which agree qualitatively with those reported in [5], [6] did not show this low field impact ionization.…”
supporting
confidence: 88%
“…Although the more recent HBT measurements [1], [2], [7], [8] covered a wider electric field range than the earlier photomultiplication measurements [4]- [6], and could not be measured on the same HBT layer, and the interpretation relied on the sim- plifying assumption that . Furthermore, these HBT results were measured on only one layer in each investigation so that errors in determining fields and multiplication factors could not easily be detected.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ng et al [4] reported high values of at fields below 200 kV cm corroborating those previously reported by [2], [3] deduced from measurements on n-p-n HBTs with In Ga As base and collector layers. derived from p-n-p HBT measurements [13], [14] and photomultiplication measurements [4], [10]- [12] did not show any low field ionization, but Ng et al [4] reported marginally lower values of . The determination of at low field in p-i-n and HBT structures is fraught with complications.…”
Section: Introductionmentioning
confidence: 89%